Personality Traits, Self-Efficacy, Family Support And Knowledge Of Illness As Predictors Of Adaptive Coping Among Breast Cancer Patients - Udeze, Cynthia N.C.; Ezenwa, Michael O; Obi-Nwosu, Harry; Iloma, David O. (Practicum Psychologia, 2024)
The study examined personality traits, self-efficacy, family support and knowledge of illness as predictors of adaptive coping among breast cancer. A total of one hundred and fifty (150) medically diagnosed breast cancer women who were present at Nnamdi Azikiwe University and St. Charles Borromeo Hospital Onitsha and have accepted to participate formed the sample of the study. Their ages ranged from 35 years-60 years with a mean age of 40 years and standard deviation of 6.28. The Big Five Personality by John, Donahue & Kentle(1991), General Self-efficacy Scale by Jerusalem and Schwarzer (1992), Family Support Scale by Procidano and Heller (2003) and Adaptive Coping Inventory by Kohn, O’Brien-Wood, Pickering and Decicco (2003) were used for data collection. The Multiple Linear Regression Analysis was used to test the four hypotheses. The first hypothesis which started that “Personality traits would significantly and positively predict adaptive coping among breast cancer patient” was not endorsed (t=.09, p<.93). The second hypothesis which stated that “Self-efficacy would significantly and positively predict adaptive coping among breast cancer patient” was upheld (t=2.49, p<.01). The third hypothesis which stated that “Family support would significantly and positively predict adaptive coping among breast cancer patients was not sustained (t=.46, p<.64). The fourth hypothesis which stated that knowledge of illness would significantly and positively predict adaptive coping among breast cancer patients” was not upheld (t=.67, p<.51). The researcher recommended qualitative studies that dig deep into the reason behind the non-significant prediction of some of the studied variable especially personality and knowledge of illness.